Stress concentration factor and hot spot stress studies of partially overlapped circular hollow section K-joints - Thong, Sopha (2010)
Circular hollow sections (CHS) are widely adopted in fixed jacket and topside structures due to their excellent structural and mechanical properties. Virtually in almost all off-shore structures, one of the main design considerations when using CHS is to optimize the structural joints which are susceptible to fatigue failure due the dynamic and cyclic loading natural of the structures. Recently, partially overlapped CHS tubular K-joints become more and more popular due to their optimum strengths when compared to other alternative joint configurations such as non-overlapped (gapped) or completely overlapped K-joints. However, in the past, few research works were carried out to study the fatigue behaviour of partially overlapped CHS K-joints. In fact, currently, only a very limited information regarding the fatigue life of CHS overlapped K-joints are available. Hence, there is a need to investigate the stress concentration factors (SCF) and the hot spot stress (HSS) distributions of this kind of joints in the current research.